Adoption of environmental innovations: Analysis from the Waipara wine industry - Sharon L. Forbes; Ross Cullen; Rachel Grout (Wine Economics and Policy, 2013)
The Greening Waipara Project developed and introduced a number of ecologically and environmentally-focused practices to the Waipara vineyards and wineries of North Canterbury, New Zealand. This paper describes the practices that were introduced to the Waipara wine industry as part of the Greening Waipara Project and evaluates the adoption of these environmental innovations by wine businesses. In addition, this paper examines the sustainability of these practices in terms of business costs and benefits. Data for the evaluation was obtained from a survey of vineyards and wineries in the Waipara region. Results reveal that adoption of the environmental innovations is relatively low and varies across wine growing properties. Furthermore, the costs associated with the innovations tend to outweigh the benefits gained by the businesses.
Keywords: 330; Adoption; Environment; Innovations